Efeitos de diferentes fontes de selênio no desempenho, parâmetros hematológicos e imunidade inata de tambaqui (Colossoma macropomum) - Silva, Sidney dos Santos (2021)
The intensification of fish production demands the need to seek strategies that allow the maintenance of growth and health of the animals. Therefore, the use of nutritional substances that improve immunity can benefit the fish in creation, contributing to the growth of fish activity. Among these, selenium (Se) is an important mineral with natural antioxidant properties essential to the growth and metabolism of animals. Mineral sources, such as sodium selenite, are the most common sources of selenium added to animal feed to meet nutritional requirements. However, recently, a new organic source containing analogous hydroxy-selenomethionine (2-hydroxy-4- methylselenobutanoic acid) has been developed, but, its effects on native fish species are still unknown. Therefore, the objective of this work was to investigate the effect of dietary supplementation of selenium (Se) in organic form (hydroxy-selenomethionine, OH-SeMet) in comparison with the inorganic form (sodium selenite, Na2SeO3) on animal performance, body yield and hematological parameters and innate immunity of tambaqui (Colossoma macropomum). For that, 900 tambaquis were used, with an initial weight of 360,00 g ± 0,06 g and total length of 27,03 ± 1,56 cm, randomly distributed in two excavated tanks of 800 m², subdivided with wire mesh in six units. 133 m², making a total of 12 experimental units. During 270 days of cultivation, the fish were fed with commercial feed extruded with 32% Crude Protein (CP) supplemented with 0,9 mg selenium / kg in organic (hydroxy-selenomethionine - Se-OH-Met) and inorganic (sodium selenite - Na2SeO3). During the production cycle (beginning, 45, 195 and 270 days) hematological and innate immunity parameters were analyzed. At the end of the experimental period, animal performance indexes, morphometric characteristics and carcass yield were evaluated. The design used was in randomized blocks, with each tank being considered a block, with 2 treatments x 3 repetitions. At the end, the data obtained were subjected to analysis of variance (ANOVA) and the comparisons of means performed using the Tukey test (5 %). The results showed that dietary supplementation with both sources of selenium did not affect the parameters of animal performance of tambaqui, but, throughout cultivation, increased hematocrit, hemoglobin concentration, protein profile (total proteins, albumin and globulin) and respiratory activity of leukocytes. It can be concluded from the study that the inclusion for 270 days of hydroxy-selenomethionine (OH-SeMet) and sodium selenite (Na2SeO3) at a concentration of 0,9 mg / kg in commercial feed for omnivorous fish (32% CP) (1,2 mg / kg of total selenium) can improve the health status of fish during fattening, maintaining hematological and biochemical indices and increasing innate immunological parameters. In addition, the use of organic Se (hydroxyselenomethionine, OH-SeMet) provided greater deposition of dorsal muscle, resulting in greater body yield in whole gutted fish (76,81 ± 0,21%), greater yield in fillet (32,61 ± 0,48%) and lower viscero-somatic index (VSI) (12,31 ± 0,17%).